Repositioning women and youths in the bean corridors in sub-Saharan Africa - Nchanji, Eileen Bogweh (Bioversity International and the International Center for Tropical Agriculture, 2021)
Women constitute more than 60% of bean producers across Africa, providing more than 60% of labour in bean production. Women are also involved in activities in the distribution and consumption hubs along the bean value chain. In collaboration with public and private partners, we have designed gender sensitive interventions aimed at reducing gender inequity through the provision of innovative bean-based technologies, credit and markets thus creating an enabling business environment for beans.